Implementation of Murabahah Benefits For The Benefit of The Indonesian Economy - Kholida, Maisyaro; J, Julina; H, Herlinda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Murabaha is a system of buying and selling goods developed by Islamic banks. In Islamic banks, of the many products in Islamic banks the most dominant products in Islamic banks are murabahah products, murabaha also provides many benefits to business actors in order to develop their businesses and potentially for the interests of the Indonesian economy, one of which is with the opening of lapangan New jobs and increase business income, this research uses literature study methods or literature research. The results showed that the murabahah contract was very influential for the interests of the Indonesian economy with a number of journal data and previous research that discussed this murabaha contract..